Light emitting diode device and preparation method thereof
By dropwise addition of strong alkali alcohol solution to zinc salt solution in quantum dot light emitting diode devices, zinc oxide nanoparticles are generated and electron transport layer is formed, which solves the problem of high hydroxyl shrinkage ratio after ZnO film formation in the prior art, and improves the brightness, luminescence efficiency and service life of the device.
Patent Information
- Application Number
- CN202111642120.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-12-29
AI Technical Summary
The hydroxyl shrinkage ratio of existing quantum dot light-emitting diode devices after film formation is high, which affects the conductivity of the electron transport layer and the service life of the device.
An alcohol solution of strong alkali is added dropwise to the zinc salt solution for mixing reaction to produce zinc oxide nanoparticles, which are dissolved in alcohol, applied to the surface of the quantum dot luminescent layer to form an electron transport layer, and finally the cathode is evaporated on the surface of the electron transport layer.
By controlling the activity of hydroxide ions, reducing the shrinkage ratio of the hydroxyl group after ZnO film formation, improving the film formation status of the electron transport layer, and improving the conductivity of the electron transport layer, so that the brightness and luminous efficiency of the device are effectively improved, and the service life is longer.
Smart Images

Figure CN114497405B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductors, and in particular relates to a light emitting diode device and a preparation method thereof. Background Art
[0002] Quantum dot light-emitting diodes have become a strong competitor for the next generation of display devices due to their high color saturation, adjustable light color, low energy consumption and other advantages. At present, compared with quantum dot light-emitting devices with organic transport layer structures, organic-inorganic hybrid quantum dot light-emitting diodes have better device performance, and this performance improvement is due to the application of high electron mobility zinc oxide nanoparticles.
[0003] ZnO quantum dots are n-type semiconductor materials with wide band gap (~3.3eV) and high exciton binding energy (60meV). They generally have two crystal structures: wurtzite and zinc blende. The hexagonal wurtzite structure is the most stable. In its crystal structure, one Zn atom and four O atoms are arranged in a regular tetrahedron. ZnO quantum dots have become one of the research hotspots for researchers due to their unique optical and electrical properties, non-toxicity and high redox potential.
[0004] When synthesizing ZnO using the sol-gel method, a dimethyl sulfoxide solution of zinc acetate dihydrate is usually used as a precursor, and a tetramethylammonium hydroxide ethanol solution is used as a catalyst and stirred in an atmosphere for 1 hour. This method is simple and easy to operate, but the shrinkage ratio of the hydroxyl group of the prepared ZnO film is high, which will affect the conductivity of the electron transport layer and the service life of the device.
[0005] Therefore, the existing light emitting diode devices need to be improved. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a light emitting diode device and a method for preparing the same, which is used to prepare the light emitting diode device, so that the brightness and luminous efficiency of the device are effectively improved and the service life is longer.
[0007] In one aspect of the present invention, the present invention provides a method for preparing a light emitting diode device. According to an embodiment of the present invention, the method comprises:
[0008] (1) forming a hole transport layer and a quantum dot light-emitting layer on the surface of the anode in sequence;
[0009] (2) adding the alcohol solution of the strong base dropwise to the zinc salt solution while stirring to carry out a mixing reaction to obtain a post-reaction solution;
[0010] (3) mixing the reaction liquid with the precipitant, centrifuging, and removing the supernatant to obtain zinc oxide nanoparticles;
[0011] (4) dissolving the zinc oxide nanoparticles in alcohol to obtain an alcohol solution of nano zinc oxide;
[0012] (5) applying the alcohol solution of nano zinc oxide to the surface of the quantum dot light-emitting layer and then drying it to form an electron transport layer on the surface of the quantum dot light-emitting layer;
[0013] (6) evaporating a cathode on the surface of the electron transport layer to obtain a light-emitting diode device,
[0014] Wherein, in step (2), the strong base includes at least one of KOH, NaOH, LiOH and CsOH.
[0015] According to the method for preparing a light-emitting diode device of an embodiment of the present invention, a hole transport layer and a quantum dot light-emitting layer are first formed on the surface of the anode in sequence, and then a strong base alcohol solution is added dropwise to a zinc salt solution with stirring to perform a mixing reaction, wherein the zinc salt is used to provide a zinc source for zinc oxide, the strong base provides an oxygen source, and the strong base includes at least one of KOH, NaOH, LiOH and CsOH, and the hydroxide ions provided by the base interact with the zinc ions to generate negatively charged Zn(OH)4 2- , when Zn(OH)4 2- When supersaturated, Zn is generated by dehydration reaction x O y (OH) z (z+2y+2x) - Clusters, when the size of the clusters reaches a certain critical value, ZnO will be generated, and then the reaction liquid is mixed with a precipitant, the ZnO in the solution is precipitated, and the supernatant is removed by centrifugation to obtain zinc oxide nanoparticles, and the obtained zinc oxide nanoparticles are dissolved in alcohol, and the alcohol solution of nano zinc oxide is applied to the surface of the quantum dot light-emitting layer and then dried, and an electron transport layer can be formed on the surface of the quantum dot light-emitting layer, and finally a cathode is evaporated on the surface of the electron transport layer to obtain a light-emitting diode device. The method of the present application selects a strong base including at least one of KOH, NaOH, LiOH and CsOH to replace tetramethylammonium hydroxide, and by controlling the activity of hydroxide ions, the shrinkage ratio of hydroxyl groups after ZnO film formation can be reduced, the film formation condition of the electron transport layer can be improved, and the conductivity of the electron transport layer can be improved, so that the brightness and luminous efficiency of the device are effectively improved, and the service life is longer.
[0016] In addition, the method for preparing a light-emitting diode device according to the above embodiment of the present invention may also have the following additional technical features:
[0017] In some embodiments of the present invention, in step (1), the anode is a transparent conductive glass, and the transparent conductive glass includes ITO, FTO, GAO or GZO.
[0018] In some embodiments of the present invention, in step (1), the hole transport layer includes TPD, NPB, PTT, TFB or PPV.
[0019] In some embodiments of the present invention, in step (1), the quantum dots in the quantum dot light-emitting layer include CdS, CdSe, CdS / ZnS, CdSe / CdS / ZnS, GaAs, InP, PbS / ZnS, PbSe / ZnS or CdSe / CdS / ZnS / InP.
[0020] In some embodiments of the present invention, the average size of the quantum dots is 2-10 nm.
[0021] In some embodiments of the present invention, in step (2), the concentration of zinc salt in the zinc salt solution is 0.1-0.2 mol / mL. Thus, the brightness and luminous efficiency of the device are effectively improved, and the service life is extended.
[0022] In some embodiments of the present invention, in step (2), the concentration of the strong base in the alcohol solution of the strong base is 0.1-0.3 mol / mL. Thus, the brightness and luminous efficiency of the device are effectively improved, and the service life is extended.
[0023] In some embodiments of the present invention, in step (2), the volume ratio of the alcohol solution of the strong base to the zinc salt solution is (0.5-1): (0.5-1). Thus, the brightness and luminous efficiency of the device are effectively improved, and the service life is extended.
[0024] In some embodiments of the present invention, in step (2), the zinc salt comprises zinc acetate dihydrate.
[0025] In some embodiments of the present invention, in step (2), the mixing reaction time is 30 to 90 minutes. Thus, the brightness and luminous efficiency of the device are effectively improved, and the service life is extended.
[0026] In some embodiments of the present invention, in step (2), the dripping rate of the alcohol solution of the strong base is 90-300 ml / h. Thus, the brightness and luminous efficiency of the device are effectively improved, and the service life is extended.
[0027] In some embodiments of the present invention, in step (3), the precipitant comprises at least one of ethyl acetate and heptane.
[0028] In some embodiments of the present invention, in step (5), the concentration of nano zinc oxide in the alcohol solution of nano zinc oxide is 15-60 mg / ml. Thus, the brightness and luminous efficiency of the device are effectively improved, and the service life is extended.
[0029] In some embodiments of the present invention, in step (5), the thickness of the electron transport layer is 10 to 50 nm. Thus, the brightness and luminous efficiency of the device are effectively improved, and the service life is extended.
[0030] In some embodiments of the present invention, in step (6), the cathode comprises Au, Ag, Al, In, Mg / Ag or Li / Al.
[0031] In some embodiments of the present invention, the method further includes: before sequentially forming the hole transport layer and the quantum dot light-emitting layer on the surface of the anode, pre-forming a hole injection layer on the surface of the anode, and then sequentially forming the hole transport layer and the quantum dot light-emitting layer on the surface of the hole injection layer, wherein the hole injection layer includes PEDOT:PSS.
[0032] In some embodiments of the present invention, the method further includes: before evaporating the cathode on the surface of the electron transport layer, forming an electron injection layer on the surface of the electron transport layer, and then evaporating the cathode on the surface of the electron injection layer, wherein the electron injection layer includes PEODT: at least one of PSS, WoO3, MoO3, NiO, HATCN, CuS, CuO and V2O5.
[0033] In a second aspect of the present invention, the present invention provides a light emitting diode device. According to an embodiment of the present invention, the light emitting diode device is prepared by the above method. Therefore, the light emitting diode device has high brightness and luminous efficiency and a long service life.
[0034] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0036] Figure 1 It is a schematic flow chart of a method for preparing a light emitting diode device according to an embodiment of the present invention. DETAILED DESCRIPTION
[0037] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0038] In one aspect of the present invention, the present invention provides a method for preparing a light emitting diode device. According to an embodiment of the present invention, referring to Figure 1 , the method comprising:
[0039] S100: Forming a hole transport layer and a quantum dot light-emitting layer on the anode surface in sequence
[0040] In this step, a hole transport layer and a quantum dot light emitting layer are sequentially formed on the surface of the anode. Specifically, the surface of the anode is first cleaned and surface treated to remove impurity particles on the surface of the anode and to increase the work function of the anode surface. Then, a hole transport layer solution is applied to the surface of the anode. After drying, a hole transport layer can be formed on the surface of the anode. Then, a quantum dot solution is applied to the surface of the hole transport layer. After drying, a quantum dot light emitting layer can be formed on the surface of the hole transport layer. More specifically, the impurity particles on the surface of the anode can be cleaned with a cotton swab dipped in detergent and then rinsed with clean water. Then, the anode can be immersed in deionized water and alcohol in turn and ultrasonicated for 15 to 25 minutes, preferably 20 minutes, and repeated twice. The surface of the anode is blown dry with nitrogen. The cleaned anode is treated with ultraviolet ozone for 15 to 25 minutes, preferably 20 minutes, and then placed in a glove box filled with nitrogen. The hole transport layer solution is spin-coated on the surface of the anode at a speed of 1000 to 2500 r / min and a gelling time of 35 to 45 seconds, preferably 40 seconds. It is baked on a heating platform at 105-115°C, preferably 110°C for 15-25min, preferably 20min, to form a hole transport layer on the surface of the anode, and then the quantum dot solution is spin-coated on the surface of the hole transport layer at a rotation speed of 1800-2200r / min, preferably 2000r / min, and the coating time is 35-45s, preferably 40s, and it is baked on a heating platform at 70-90°C, preferably 80°C for 15-25min, preferably 20min, to form a quantum dot light-emitting layer on the surface of the hole transport layer.
[0041] It should be noted that those skilled in the art can select the thickness and specific type of the anode, hole transport layer and quantum dot light-emitting layer according to actual needs. For example, the anode is transparent conductive glass, including but not limited to ITO, FTO, GAO or GZO; the hole transport layer includes but is not limited to TPD, NPB, PTT, TFB or PPV; the quantum dots in the quantum dot light-emitting layer include but are not limited to CdS, CdSe, CdS / ZnS, CdSe / CdS / ZnS, GaAs, InP, PbS / ZnS, PbSe / ZnS or CdSe / CdS / ZnS / InP. Furthermore, the average size of the quantum dots is 2 to 10 nm.
[0042] Further, step S100 also includes: before the hole transport layer and the quantum dot light-emitting layer are sequentially formed on the surface of the anode, a hole injection layer is pre-formed on the surface of the anode, and then the hole transport layer and the quantum dot light-emitting layer are sequentially formed on the surface of the hole injection layer. Specifically, the hole injection layer solution is applied to the surface of the anode that has been cleaned and surface-treated, and the hole injection layer can be formed on the surface of the anode after drying. More specifically, the hole injection layer solution is spin-coated on the surface of the anode that has been cleaned and surface-treated, with a rotation speed of 3800 to 4200 r / min, preferably 4000 r / min, and the gelling time is 35 to 45 s, preferably 40 s, and it is baked on a heating platform at 135 to 145°C, preferably 140°C for 8 to 12 min, preferably 10 min, to form a hole injection layer on the surface of the anode. The specific method of sequentially forming the hole transport layer and the quantum dot light-emitting layer on the surface of the hole injection layer is the same as described above, and will not be repeated here. It should be noted that those skilled in the art can select the thickness and specific type of the hole injection layer according to actual needs. For example, the hole injection layer includes but is not limited to PEDOT:PSS.
[0043] S200: Add the alcohol solution of the strong base to the zinc salt solution with stirring to carry out a mixed reaction
[0044] In this step, under atmospheric conditions, the alcohol solution of the strong base is slowly added dropwise to the zinc salt solution with stirring (the stirring method is not limited) to carry out a mixing reaction, wherein the zinc salt is used to provide a zinc source for zinc oxide, the strong base provides an oxygen source, and the strong base includes at least one of KOH, NaOH, LiOH and CsOH. The hydroxide ions provided by the base interact with the zinc ions to generate negatively charged Zn(OH)4 2- , when Zn(OH)4 2- When supersaturated, Zn is generated by dehydration reaction x O y (OH) z (z+2y+2x) -The inventors found that by selecting a strong base including at least one of KOH, NaOH, LiOH and CsOH to replace tetramethylammonium hydroxide, the shrinkage ratio of the hydroxyl group after ZnO film formation can be reduced by controlling the activity of the hydroxide ions, the film formation of the electron transport layer can be improved, and the conductivity of the electron transport layer can be improved, so that the brightness and luminous efficiency of the device are effectively improved, and the service life is longer.
[0045] Furthermore, in the above zinc salt solution, the concentration of zinc salt is 0.1-0.2 mol / mL. The inventors found that if the concentration of zinc salt is too low, the output of ZnO is low and the particles are small; while if the concentration of zinc salt is too high, the output of ZnO particles is large. Therefore, by adopting the zinc salt concentration of the present application, the output of ZnO is high and the particle size is appropriate.
[0046] Furthermore, in the alcohol solution of the strong base, the concentration of the strong base is 0.1-0.3 mol / mL. The mixing volume ratio of the alcohol solution of the strong base and the zinc salt solution is (0.5-1):(0.5-1).
[0047] Furthermore, the mixing reaction time is 10 to 90 minutes. The inventors have found that if the mixing reaction time is too short, the reaction is incomplete and the ZnO particles are of different sizes; and if the mixing reaction time is too long, the ZnO particles are too large. Therefore, the mixing reaction time of the present application is conducive to obtaining ZnO particles with suitable and uniform particle sizes.
[0048] Furthermore, the dripping rate of the alcohol solution of the strong base is 90-300 ml / h. The inventors found that if the alcohol solution of the strong base is dripped too slowly, the ZnO particles will be too large; and if the alcohol solution of the strong base is dripped too quickly, the ZnO particles will be uneven. Therefore, the dripping rate of the present application is conducive to obtaining ZnO particles with appropriate and uniform particle size.
[0049] It should be noted that the specific types of the above-mentioned zinc salt, the solvent of the zinc salt solution and the alcohol are not particularly limited, and those skilled in the art can select them according to actual needs. For example, the zinc salt includes but is not limited to zinc acetate dihydrate; the solvent of the zinc salt solution includes but is not limited to dimethyl sulfoxide; the alcohol includes but is not limited to ethanol.
[0050] S300: Mix the reaction solution with the precipitant, centrifuge, and remove the supernatant
[0051] In this step, the reaction liquid obtained in step S200 is mixed with a precipitant and then centrifuged to precipitate ZnO in the solution, and the supernatant is removed by centrifugation to obtain zinc oxide nanoparticles. It should be noted that those skilled in the art can select the specific type of the above-mentioned precipitant according to actual needs, for example, the precipitant includes but is not limited to at least one of ethyl acetate and heptane. In addition, the mixing ratio of the reaction liquid and the precipitant is not particularly limited, and those skilled in the art can select it according to actual needs, as long as the ZnO in the reaction liquid can be completely precipitated.
[0052] S400: Dissolving zinc oxide nanoparticles in alcohol
[0053] In this step, the zinc oxide nanoparticles obtained in step S300 are dissolved in alcohol to obtain an alcohol solution of nano zinc oxide. It should be noted that the specific type of alcohol is the same as described above and will not be repeated here.
[0054] S500: Apply the alcohol solution of nano zinc oxide to the surface of the quantum dot light-emitting layer and then dry it
[0055] In this step, the electron transport layer can be formed on the surface of the quantum dot light-emitting layer by applying the alcohol solution of nano zinc oxide to the surface of the quantum dot light-emitting layer and then drying it. Specifically, the alcohol solution of nano zinc oxide is spin-coated on the surface of the quantum dot light-emitting layer at a speed of 1800 to 2200 r / min, preferably 2000 r / min, and the coating time is 35 to 45 seconds, preferably 40 seconds, and it is baked on a heating platform at 140 to 150° C., preferably 145° C. for 25 to 35 minutes, preferably 30 minutes, to form the electron transport layer on the surface of the quantum dot light-emitting layer.
[0056] Furthermore, in the alcohol solution of nano zinc oxide, the concentration of nano zinc oxide is 15 to 60 mg / ml. The thickness of the electron transport layer is 10 to 50 nm. The inventors found that if the thickness of the electron transport layer is too small, the brightness of the light-emitting diode device is low; and if the thickness of the electron transport layer is too large, it will affect the imaging of the light-emitting diode device after it is lit. Therefore, by adopting the thickness of the electron transport layer of the present application, the brightness of the light-emitting diode device is higher and the imaging effect is better.
[0057] S600: Evaporation of cathode on the surface of electron transport layer
[0058] In this step, a light-emitting diode device can be obtained by evaporating a cathode on the surface of the electron transport layer. Specifically, the substrate obtained in step S500 is placed in an evaporation chamber with a vacuum degree of 2×10~3×10Pa, and the cathode is evaporated by thermal evaporation. The thickness and evaporation rate of the film are monitored by a quartz crystal film thickness meter. It should be noted that those skilled in the art can select the thickness and specific type of the cathode according to actual needs. For example, the cathode includes but is not limited to Au, Ag, Al, In, Mg / Ag or Li / Al.
[0059] Furthermore, step S600 also includes: before evaporating the cathode on the surface of the above-mentioned electron transport layer, pre-forming an electron injection layer on the surface of the electron transport layer, and then evaporating the cathode on the surface of the electron injection layer. Specifically, the electron injection layer can be deposited by evaporation technology or sputtering technology. It should be noted that the thickness and specific type of the electron injection layer are not particularly limited, and those skilled in the art can choose according to actual needs. For example, the electron injection layer includes but is not limited to at least one of PEODT:PSS, WoO3, MoO3, NiO, HATCN, CuS, CuO and V2O5.
[0060] The inventors found that by first forming a hole transport layer and a quantum dot light-emitting layer on the surface of the anode in sequence, and then adding a strong base alcohol solution dropwise to a zinc salt solution with stirring for a mixed reaction, wherein the zinc salt is used to provide a zinc source for zinc oxide, and the strong base provides an oxygen source, and the strong base includes at least one of KOH, NaOH, LiOH and CsOH, and the hydroxide ions provided by the base interact with the zinc ions to first generate negatively charged Zn(OH)4 2- , when Zn(OH)4 2- When supersaturated, Zn is generated by dehydration reaction x O y (OH) z (z+2y+2x) - Clusters, when the size of the clusters reaches a certain critical value, ZnO will be generated, and then the reaction liquid is mixed with a precipitant, the ZnO in the solution is precipitated, and the supernatant is removed by centrifugation to obtain zinc oxide nanoparticles, and the obtained zinc oxide nanoparticles are dissolved in alcohol, and the alcohol solution of nano zinc oxide is applied to the surface of the quantum dot light-emitting layer and then dried, and an electron transport layer can be formed on the surface of the quantum dot light-emitting layer, and finally a cathode is evaporated on the surface of the electron transport layer to obtain a light-emitting diode device. The method of the present application selects a strong base including at least one of KOH, NaOH, LiOH and CsOH to replace tetramethylammonium hydroxide, and by controlling the activity of hydroxide ions, the shrinkage ratio of hydroxyl groups after ZnO film formation can be reduced, the film formation condition of the electron transport layer can be improved, and the conductivity of the electron transport layer can be improved, so that the brightness and luminous efficiency of the device are effectively improved, and the service life is longer.
[0061] In a second aspect of the present invention, the present invention provides a light emitting diode device. According to an embodiment of the present invention, the light emitting diode device is prepared by the above method. Therefore, the light emitting diode device has high brightness and luminous efficiency and a long service life. It should be noted that the features and advantages described above for the method for preparing the light emitting diode device are also applicable to the light emitting diode device, and will not be repeated here.
[0062] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0063] Example 1
[0064] Step 1: Use absorbent cotton to soak in detergent to clean the impurities on the surface of ITO (thickness 1.1mm), and then rinse with clean water. Then immerse the substrate in deionized water and alcohol for 20 minutes each, repeat twice, and then blow dry the substrate surface with nitrogen. Finally, treat the cleaned ITO substrate with ultraviolet ozone for 20 minutes.
[0065] Step 2: In the room temperature atmosphere, spin-coat PEDOT:PSS on the surface of the ITO substrate at a speed of 4000r / min, the coating time is 40s, and bake on a heating platform at 140℃ for 10min to form a hole injection layer (40nm thick) on the surface of the ITO substrate.
[0066] Step 3: Place the substrate in a nitrogen-filled glove box, spin-coat TFB dissolved in chlorobenzene solution on the surface of the dried PEDOT:PSS at a speed of 2000 r / min and a coating time of 40 s, and bake it on a heating platform at 110°C for 20 min to form a hole transport layer (30 nm thick) on the surface of the hole injection layer.
[0067] Step 4: Next, spin-coat CdSe / CdS / ZnS / InP quantum dots (the average size of the quantum dots is 6 nm) dissolved in toluene solution on the surface of TFB at a rotation speed of 2000 r / min and a coating time of 40 s, and bake on a heating platform at 80°C for 20 min to form a quantum dot light-emitting layer (with a thickness of 20 nm) on the surface of the hole transport layer.
[0068] Step 5: Weigh 3 mol of zinc acetate dihydrate and dissolve it in 30 mL of dimethyl sulfoxide solution as a precursor, and weigh 3.1 mol of KOH and dissolve it in 30 mL of anhydrous ethanol as a catalyst. In an atmospheric environment, slowly and evenly add the prepared catalyst (drop rate of 90 ml / h) to the precursor solution and stir for 1 hour. Then put the reaction liquid in a centrifuge tube, add 200 ml of ethyl acetate solution to make it turbid, and pour off the supernatant after centrifugation to obtain zinc oxide nanoparticles.
[0069] Step 6: Add a small amount of anhydrous ethanol to dissolve the zinc oxide nanoparticles, filter and obtain a ZnO ethanol solution, take a small amount of the ZnO ethanol solution, dry and calculate the concentration, and then add anhydrous ethanol to obtain a 30 mg / mL ZnO ethanol solution.
[0070] Step 7: Spin-coat a ZnO (30 mg / mL) solution dissolved in ethanol on the surface of the quantum dot light-emitting layer. The coating time is 40 s, the rotation speed is 2000 r / min, and it is baked on a heating platform at 145°C for 30 min to form an electron transport layer (20 nm thick) on the surface of the quantum dot light-emitting layer.
[0071] Step 8: Place the substrate into a vapor deposition chamber with a vacuum degree of 2×10Pa, and use thermal evaporation to deposit a metal aluminum electrode (thickness of 90nm) to obtain a light-emitting diode device. This device is device 1, and its performance characterization is shown in Table 1.
[0072] Example 2
[0073] Step 1: Use absorbent cotton to wash away impurities on the surface of FTO (thickness 1.1mm), and then rinse with clean water. Then immerse the substrate in deionized water and alcohol for 20 minutes each, repeat twice, and then blow dry the substrate surface with nitrogen. Finally, treat the cleaned FTO substrate with UV ozone for 20 minutes.
[0074] Step 2: Place the substrate in a nitrogen-filled glove box, spin-coat PTT dissolved in chlorobenzene solution on the surface of the FTO substrate at a speed of 2000 r / min and a coating time of 40 s, and bake it on a heating platform at 110°C for 20 min to form a hole transport layer (30 nm thick) on the surface of the FTO substrate.
[0075] Step 3: Next, spin-coat PbS / ZnS quantum dots (the average size of the quantum dots is 5 nm) dissolved in toluene solution on the PTT surface at a rotation speed of 2000 r / min and a coating time of 40 s, and bake on a heating platform at 80°C for 20 min to form a quantum dot light-emitting layer (with a thickness of 20 nm) on the surface of the hole transport layer.
[0076] Step 4: Weigh 3 mol of zinc acetate dihydrate and dissolve it in 30 mL of dimethyl sulfoxide solution as a precursor, and weigh 3 mol of LiOH and dissolve it in 30 mL of anhydrous ethanol as a catalyst. In an atmospheric environment, slowly and evenly add the prepared catalyst (drop rate of 90 ml / h) to the precursor solution and stir for 1 hour. Then put the reaction liquid in a centrifuge tube, add 200 ml of ethyl acetate solution to make it turbid, and pour off the supernatant after centrifugation to obtain zinc oxide nanoparticles.
[0077] Step 5: Add a small amount of anhydrous ethanol to dissolve the zinc oxide nanoparticles, filter and obtain a ZnO ethanol solution, take a small amount of the ZnO ethanol solution, dry and calculate the concentration, and then add anhydrous ethanol to obtain a 20 mg / mL ZnO ethanol solution.
[0078] Step 6: Spin-coat a ZnO 20 mg / mL solution dissolved in ethanol on the surface of the quantum dot light-emitting layer. The coating time is 40 s, the rotation speed is 2000 r / min, and the solution is baked on a heating platform at 145°C for 30 min to form an electron transport layer (15 nm thick) on the surface of the quantum dot light-emitting layer.
[0079] Step 7: Place the substrate into a vapor deposition chamber with a vacuum degree of 2×10Pa, and use thermal evaporation to deposit a metal silver electrode (thickness of 90nm) to obtain a light-emitting diode device. This device is device 2, and its performance characterization is shown in Table 1.
[0080] Example 3
[0081] Step 1: Use absorbent cotton to wash off the impurities on the surface of GZO (thickness 1.1mm), and then rinse with clean water. Then immerse the substrate in deionized water and alcohol for 20 minutes each, repeat twice, and then blow dry the substrate surface with nitrogen. Finally, treat the cleaned GZO substrate with ultraviolet ozone for 20 minutes.
[0082] Step 2: Place the substrate in a nitrogen-filled glove box, spin-coat TPD dissolved in chlorobenzene solution on the surface of the FTO substrate at a speed of 2500 r / min and a coating time of 40 s, and bake it on a heating platform at 110°C for 20 min to form a hole transport layer (30 nm thick) on the surface of the GZO substrate.
[0083] Step 3: Next, spin-coat CdS quantum dots (the average size of the quantum dots is 3 nm) dissolved in toluene solution on the TPD surface at a rotation speed of 2000 r / min and a coating time of 40 s, and bake on a heating platform at 80°C for 20 min to form a quantum dot light-emitting layer (with a thickness of 20 nm) on the surface of the hole transport layer.
[0084] Step 4: Weigh 3 mol of zinc acetate dihydrate and dissolve it in 30 mL of dimethyl sulfoxide solution as a precursor, and weigh 3.5 mol of NaOH and dissolve it in 30 mL of anhydrous ethanol as a catalyst. In an atmospheric environment, slowly and evenly add the prepared catalyst (drop rate of 90 ml / h) to the precursor solution and stir for 1 hour. Then put the reaction liquid in a centrifuge tube, add 200 ml of ethyl acetate solution to make it turbid, centrifuge and pour off the supernatant to obtain zinc oxide nanoparticles.
[0085] Step 5: Add a small amount of anhydrous ethanol to dissolve the zinc oxide nanoparticles, filter and obtain a ZnO ethanol solution, take a small amount of the ZnO ethanol solution, dry and calculate the concentration, and then add anhydrous ethanol to obtain a 60 mg / mL ZnO ethanol solution.
[0086] Step 6: Spin-coat a ZnO (60 mg / mL) solution dissolved in ethanol on the surface of the quantum dot light-emitting layer. The coating time is 40 s, the rotation speed is 2000 r / min, and it is baked on a heating platform at 145°C for 30 min to form an electron transport layer (30 nm thick) on the surface of the quantum dot light-emitting layer.
[0087] Step 7: Deposit an electron injection layer PEODT:PSS (thickness 40 nm).
[0088] Step 8: Place the substrate into a vapor deposition chamber with a vacuum degree of 2×10Pa, and use thermal evaporation to deposit a metal aluminum electrode (thickness of 90nm) to obtain a light-emitting diode device. This device is device three, and its performance characterization is shown in Table 1.
[0089] Comparative Example
[0090] The difference from Example 2 is that the strong base used in step 4 is tetramethylammonium hydroxide, and the rest is the same as Example 2. The light emitting diode obtained has a higher efficiency but a much shorter lifespan than Example 2.
[0091] Table 1 Performance characteristics of the light emitting diode devices prepared in Examples 1 to 3 and Comparative Examples
[0092]
[0093]
[0094] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0095] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a light emitting diode device, characterized in that: include: (1) forming a hole transport layer and a quantum dot light-emitting layer on the surface of the anode in sequence; (2) adding the alcohol solution of the strong base dropwise to the zinc salt solution while stirring to carry out a mixing reaction to obtain a post-reaction solution; (3) mixing the reaction liquid with the precipitant, centrifuging, and removing the supernatant to obtain zinc oxide nanoparticles; (4) dissolving the zinc oxide nanoparticles in alcohol to obtain an alcohol solution of nano zinc oxide; (5) applying the alcohol solution of nano zinc oxide to the surface of the quantum dot light-emitting layer and then drying it to form an electron transport layer on the surface of the quantum dot light-emitting layer; (6) evaporating a cathode on the surface of the electron transport layer to obtain a light-emitting diode device, Wherein, in step (2), the strong base includes at least one of KOH, NaOH, LiOH and CsOH, In the zinc salt solution, the concentration of zinc salt is 0.1-0.2 mol / mL; In the alcohol solution of the strong base, the concentration of the strong base is 0.1 to 0.3 mol / mL; The mixing volume ratio of the alcohol solution of the strong base and the zinc salt solution is (0.5-1): (0.5-1); The dropping rate of the alcohol solution of the strong base is 90-300 ml / h.
2. The method according to claim 1, characterized in that In step (1), the anode is a transparent conductive glass, and the transparent conductive glass includes ITO, FTO, GAO or GZO; Optionally, in step (1), the hole transport layer comprises TPD, NPB, PTT, TFB or PPV.
3. The method according to claim 1, characterized in that In step (1), the quantum dots in the quantum dot light-emitting layer include CdS, CdSe, CdS / ZnS, CdSe / CdS / ZnS, GaAs, InP, PbS / ZnS, PbSe / ZnS or CdSe / CdS / ZnS / InP; Optionally, the average size of the quantum dots is 2 to 10 nm.
4. The method according to claim 1, characterized in that: In step (2), the zinc salt includes zinc acetate dihydrate; Optionally, in step (2), the mixing reaction time is 10 to 90 minutes.
5. The method according to claim 1 or 4, characterized in that: In step (3), the precipitant includes at least one of ethyl acetate and heptane.
6. The method according to claim 1 or 4, characterized in that: In step (5), the concentration of nano zinc oxide in the alcohol solution of nano zinc oxide is 15 to 60 mg / ml; Optionally, in step (5), the thickness of the electron transport layer is 10 to 50 nm.
7. The method according to claim 1, characterized in that In step (6), the cathode includes Au, Ag, Al, In, Mg / Ag or Li / Al.
8. The method according to claim 1, characterized in that Further including: Before the hole transport layer and the quantum dot light emitting layer are sequentially formed on the surface of the anode, a hole injection layer is preliminarily formed on the surface of the anode, and then the hole transport layer and the quantum dot light emitting layer are sequentially formed on the surface of the hole injection layer. Wherein, the hole injection layer includes PEDOT:PSS.
9. The method according to claim 8, characterized in that Further including: Before evaporating the cathode on the surface of the electron transport layer, an electron injection layer is preliminarily formed on the surface of the electron transport layer, and then the cathode is evaporated on the surface of the electron injection layer. Wherein, the electron injection layer includes at least one of PEODT:PSS, WoO3, MoO3, NiO, HATCN, CuS, CuO and V2O5.
10. A light emitting diode device, characterized in that: The method according to any one of claims 1 to 9 is used to prepare the present invention.
Citation Information
Patent Citations
Quantum dot light-emitting diode and preparation method thereof
CN113130833A